Amerindian Rebirth : Reincarnation Belief Among North American Indians and Inuit - Slobodin, Richard, 1915-2005; Mills, Antonia Curtze (Book collections on Project MUSE., 1994)
"Until now few people have been aware of the prevalence of belief in some form of rebirth or reincarnation among North American native peoples. This collection of essays by anthropologists and one psychiatrist examines this concept among native American societies, from near the time of contact until the present day. Amerindian Rebirth opens with a foreword by Gananath Obeyesekere that contrasts North American and Hindu Buddhist Jain beliefs. The introduction gives an overview, and the first chapter summarizes the context, distribution, and variety of recorded belief. All the papers chronicle some aspect of rebirth belief in a number of different cultures. Essays cover such topics as seventeenth-century Huron eschatology, Winnebago ideology, varying forms of Inuit belief, and concepts of rebirth found among subarctic natives and Northwest Coast peoples. The closing chapters address the genesis and anthropological study of Amerindian reincarnation. In addition, the possibility of evidence for the actuality of rebirth is addressed. Amerindian Rebirth will further our understanding of concepts of self-identity, kinship, religion, cosmology, resiliency, and change among native North American peoples."--Publisher website.